MEDIA TEXTS FROM A COGNITIVE LINGUISTIC PERSPECTIVE - Musaxonova Mohigul Avazxon qizi (Western European Studies, 2024)
In this article, a new field of modern linguistics, media-linguistics, researches the scientific discussion of the issues of media text, media speech stylistics. In this, the opinions on the research of the issue of media stylistics in English linguistics in cognitive linguistics are expressed.
Keywords: cognitive linguistics; media discourse; medialinguistics